The Impact of Website Quality on Customer Satisfaction at Grand Grafika Medan: Pengaruh Kualitas Website terhadap Kepuasan Pelanggan di Grand Grafika Medan - Rafika S. Sembiring; Thamrin; Victor Saputra Ginting (Universitas Muhammadiyah Palu, 2023)
Internet and virtual communities have transformed consumers, societies, and corporations with wide spread access to information, better social networking and enhanced communication abilities. One of the internet networking is website. The website which link millions of users from all over the world with same interests, views and hobbies. The research is conducted at Grand Grafika Medan. The preliminary data given by the owner of Grand Grafika Medan that the orders and transactions by website have several matters which the customers are not satisfied with the website quality and responds from the company. The objectives of the research are to find out whether website quality has impact on customer satisfaction and how strong the impact of website quality on customer satisfaction at Grand Grafika Medan. The population that is used in the research is the customers of Grand Grafika Medan that are 93 people. The sampling technique is simple random sampling which the customers have same chance to be chosen as sample. In analyzing questionnaires, the writer used validity test and reliability test, to analyze the data, use statistics, correlation test, determination test, linear regression, and hypothesis test. The correlation test shows Website Quality have a positive and significantly strong impact on employees’ customer satisfaction at Grand Grafika Medan. zcount > ztable (8.10 > 1.96), This means the Null hypothesis (Ho) is rejected and the alternative (Ha) is accepted. Website Quality have impact on employees’ customer satisfaction at Grand Grafika Medan. After analysis and results, the writer give several recommendations to the company.